Effects of Read-Aloud Folklore on Character Development and Regional Literary Literacy Among Parents and Children - Bashori, Muzakki; Cahyono, Rizki Aldi; Sophianti, Naia; Wardati, Mutiara; Rakhmanto, Bambang; Rahmawati, Eni; Aprilia, Dwi Pangesti; Rohman, Muhammad Mujibur (Anaphora : Journal of Language, Literary, and Cultural Studies, 2025)
The globalization era presents challenges in preserving the existence, sustainability, and authenticity of local literary heritage, including folklore. Today, folklore is gradually fading and becoming less familiar among younger generations. However, regional literary literacy plays an essential role in building and maintaining the cultural identity of a community and contributes to fostering positive character development in children from an early age. Recognizing the central role of regional literary literacy in shaping children’s growth and development, it is crucial to internalize positive values derived from folklore amidst moral decadence. Responding to the duality between modernity and the preservation of local wisdom, this study aims to highlight the significant relevance of strengthening regional literature through the read-aloud method. The research focuses on teachers and parents of students at SD Negeri Pakintelan 03 Gunungpati, Semarang, Central Java. “Ketika Nasi Menangis”, a trilingual book developed in Indonesian, Javanese, and English, was used as a medium to support this research. The findings indicate that reading folklore aloud has a positive impact on children’s character development in general and the enhancement of regional literary literacy in particular. For parents and teachers, this study has fostered their understanding of the importance of bedtime storytelling through the read-aloud folklore method, encouraged enthusiasm for narrating bedtime stories, and provided a practical guide for effective storytelling.